2016
DOI: 10.1073/pnas.1514511113
|View full text |Cite
|
Sign up to set email alerts
|

Prolongevity hormone FGF21 protects against immune senescence by delaying age-related thymic involution

Abstract: Age-related thymic degeneration is associated with loss of naïve T cells, restriction of peripheral T-cell diversity, and reduced healthspan due to lower immune competence. The mechanistic basis of age-related thymic demise is unclear, but prior evidence suggests that caloric restriction (CR) can slow thymic aging by maintaining thymic epithelial cell integrity and reducing the generation of intrathymic lipid. Here we show that the prolongevity ketogenic hormone fibroblast growth factor 21 (FGF21), a member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 47 publications
2
81
0
1
Order By: Relevance
“…It is therefore possible that the above-mentioned exaggerated growth and bone phenotypes [90,135] are due to the differences in whole-body energy balance between gain/loss of function and na€ ıve animals rather than resulting from direct action of FGF21. Consistent with this hypothesis, it has been reported that mice with forced FGF21 overexpression do not have a higher risk of bone fractures [6,75,115]. Finally, FGF21 is a potent regulator of body weight [60,76], and weight management is independently known to have a considerable physiological impact on bone turnover [142,143].…”
Section: Adverse Effects Of Fgf21: Torpor Reproduction and Bone Turnmentioning
confidence: 71%
See 1 more Smart Citation
“…It is therefore possible that the above-mentioned exaggerated growth and bone phenotypes [90,135] are due to the differences in whole-body energy balance between gain/loss of function and na€ ıve animals rather than resulting from direct action of FGF21. Consistent with this hypothesis, it has been reported that mice with forced FGF21 overexpression do not have a higher risk of bone fractures [6,75,115]. Finally, FGF21 is a potent regulator of body weight [60,76], and weight management is independently known to have a considerable physiological impact on bone turnover [142,143].…”
Section: Adverse Effects Of Fgf21: Torpor Reproduction and Bone Turnmentioning
confidence: 71%
“…In humans, circulating levels of FGF21 were shown to be generally higher in metabolically compromised states [70][71][72][73], suggestive of a biological connection to disease [74]. Finally, production of FGF21 in the thymus was recently linked to the prevention of age-related tissue degeneration [75].…”
Section: Introductionmentioning
confidence: 99%
“…This chemical improves the immune reconstitution during carcinogenesis (Bhattacharyya et al 2007(Bhattacharyya et al , 2010 and prevents deltamethrin-induced thymocyte apoptosis by arresting the oxidative stress through caspasedependent signaling pathways (Kumar et al 2015). Fibroblast growth factor 21 (FGF21) plays a critical role in the regulation of energy metabolism (Salminen et al 2016) and protects against age-associated thymic involution by increasing the cortical TEC and thymocyte progenitors in mice (Youm et al 2016). Pharmacological administration of FGF7 or keratinocyte growth factor (KGF) represses the Ink4a tumor-suppressor gene and partially rejuvenates the murine thymocyte progenitors (Berent-Maoz et al 2012).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%
“…C57BL/6J (B6) mice are relatively long-lived, with an average lifespan of approximately 884 days (2.4 years or 29 months), whereas BALB/c mice live for only 732 days (2 years or 24 months) on average [31]. To model the aging human immune system in mice, preclinical researchers have routinely used mice between 16-24 months of age [12, 20, 27, 32]. These are chronologically equivalent to U.S. citizens at 43-66 years old based on the average life expectancy of 79 years according to the Centers for Disease Control (CDC).…”
Section: Modeling Old Age In Micementioning
confidence: 99%